Cemiplimab in an Elderly Frail Population of Patients With Locally Advanced or Metastatic Cutaneous Squamous Cell Carcinoma: A Single-Center Real-Life Experience From Italy - Strippoli, Sabino; Fanizzi, Annarita; Quaresmini, Davide; Nardone, Annalisa; Armenio, Andrea; Figliuolo, Francesco; Filotico, Raffaele; Fucci, Livia; Mele, Fabio; Traversa, Michele; De Luca, Federica; Montagna, Elisabetta Sara; et al. (Frontiers in Oncology, 2021)
Cutaneous squamous cell carcinoma (CSCC) is the second most common skin cancer whose incidence is growing parallel to lengthening of average lifespan. Cemiplimab, an antiPD-1 monoclonal antibody, is the first approved immunotherapy for patients with locally advanced (laCSCC) or metastatic (mCSCC) CSCC thanks to phase I-II studies showing high antitumor activity and good tolerability. Nevertheless, at present very few data are available regarding cemiplimab in real life experience and in frail, elderly and immunosuppressed patients as well as regarding biomarkers able to predict response guiding therapeutic choices. We built a retroprospective cohort study including 30 non-selected patients with laCSCC (25) and mCSCC (5) treated with cemiplimab from August 2019 to November 2020. Clinical outcomes, toxicity profile and correlations with disease, patients and blood parameters are explored. Median age was 81 years (range 36-95); 24 males; 5 patients having an immunosuppressive condition while frailty prevalence was 83% based on index deriving from age, ECOG performance status and Charlson Comorbidity Index. We reported 23 responses (76.7%) with 9 CR (30%). A significant higher response rate was observed in head and neck primary tumours and in patients with haemoglobin level >12 g/dL. No difference was observed with respect to frailty, median age, sex, body mass index. Baseline low neuthophils/lymphocytes ratio and low platelets/lymphocytes ratio resulted also correlated with a better response. Moreover, lymphocytes, neutrophils and monocytes behaviors had an opposite trend in responders and non-responders. An overall response was reported in 4 of 5 immunosuppressed patients. Seventeen patients (57.6%) have an ongoing response and are still alive. Six responders interrupted treatment (2 for toxicity and 4 for personal choice) but maintaining their response. The treatment was well tolerated by the majority of patients. The most common adverse events were fatigue in 7 patients (23.3%) and skin toxicity in 10 patients (33.3%) including pruritus in 6 patients, rash in 3 patients, bullous erythema in 1 patient. In our real-life experience, cemiplimab showed high antitumor activity with acceptable safety profile similar to those in selected patients of trials. Moreover, its antitumor activity resulted not impaired in very elderly patients and in those with immunocompromised status.